2019
DOI: 10.4103/njs.njs_40_18
|View full text |Cite
|
Sign up to set email alerts
|

Early experience with ligasure thyroidectomy in a Nigeria Teaching Hospital

Abstract: Background: The principles of safe and efficient thyroid surgery had been established and the technique has remained the same for over the century without any major significant changes. The introductions of electrosurgical devices constitute a major shift in the technique of thyroid surgery. Objective: We present our early experience with the use of LIGASURE vessel sealing system for the procedure of thyroidectomy. Materials and Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…It provides effective hemostasis by sealing tiny blood vessel up to 7 mm in the bed of thyroid gland. In conventional suture tie thyroidectomy these vessels continue to ooze because they cannot be ligated for control of bleeding [27][28]. Since LigaSure operates at a lower temperature (80°F) as compared to other EBDs like Harmonic Focus, it causes reduced thermal damage [26][27].…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® mentioning
confidence: 99%
See 1 more Smart Citation
“…It provides effective hemostasis by sealing tiny blood vessel up to 7 mm in the bed of thyroid gland. In conventional suture tie thyroidectomy these vessels continue to ooze because they cannot be ligated for control of bleeding [27][28]. Since LigaSure operates at a lower temperature (80°F) as compared to other EBDs like Harmonic Focus, it causes reduced thermal damage [26][27].…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® mentioning
confidence: 99%
“…Use of LigaSure in thyroid surgery significantly decreases risk of detrimental vascular and nerve damage. In comparison to conventional thyroidectomy, LigaSure vessel sealing system has been suggested to reduce operative time, RLN, and parathyroid injury [27].…”
Section: The Effectiveness and Safety Of Ebds Like Harmonic-scalpel® mentioning
confidence: 99%
“…Accomplishing meticulous hemostasis is essential to avoid serious complications yet the thyroid gland has been stated as a highly vascularized organ. Onwards of the recent introduction of various surgical energy devices such as LSJ vessel sealing systems and harmonic devices in order for the procedures of thyroidectomy, physicians have encountered some propounding advantages [15][16][17]. As such, some authors asserted that utilization of most used energy-based devices: (i) Ultrasonic Harmonic Focus Scalpel (HF), (ii) LSJ, and (iii) Thunderbeat Open Fine Jaw (TB) are effective and even safe in both hemostasis and dissection nearby the course of the inferior laryngeal nerve and even the suspensory Ligament of Berry.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of the study by Qandili et al and a meta-analysis ( 22), the post-surgical drainage in thyroidectomy did not offer any significant advantage on seroma. Arowolo et al (24) reported two cases of seroma in 30 patients undergoing surgery. However, in the stated study, the head of bed was tilted upwards to 15 degrees in an opposite direction from the Trendelenburg position; moreover, thyroidectomy was performed using the ligation technique.…”
Section: Discussionmentioning
confidence: 99%